The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ijms21228628
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective Effects of Alpha-1 Antitrypsin against Tacrolimus-Induced Renal Injury

Abstract: The protective effects of alpha-1 antitrypsin (AAT) in tacrolimus (TAC)-induced renal injury was evaluated in a rat model. The TAC group rats were subcutaneously injected with 2 mg/kg TAC every day for four weeks. The TAC with AAT group was cotreated with daily subcutaneous injections of TAC and intraperitoneal injections of AAT (80 mg/kg) for four weeks. The effects of AAT on TAC-induced renal injury were evaluated using serum biochemistry, histopathology, and Western blotting. The TAC injection significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
(55 reference statements)
2
3
0
Order By: Relevance
“…Our results have revealed that the renal content of TGFβ-1, as well as the protein expression of α-SMA and collagen type1, increased following TAC treatment. These align with the results published by Lim et al [ 1 ], where the immunostaining of fibrotic markers collagen, fibronectin, and α-SMA increased in the TAC group. In addition, the study of Ume and colleagues [ 31 ] showed that tacrolimus-treated renal fibroblasts displayed fibroblast-to-myofibroblast transition phenotyping, which was demonstrated by α-smooth muscle actin, and collagen type IV overexpression accompanied by concomitant induction of TGF-β1 ligand secretion, and receptor activation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results have revealed that the renal content of TGFβ-1, as well as the protein expression of α-SMA and collagen type1, increased following TAC treatment. These align with the results published by Lim et al [ 1 ], where the immunostaining of fibrotic markers collagen, fibronectin, and α-SMA increased in the TAC group. In addition, the study of Ume and colleagues [ 31 ] showed that tacrolimus-treated renal fibroblasts displayed fibroblast-to-myofibroblast transition phenotyping, which was demonstrated by α-smooth muscle actin, and collagen type IV overexpression accompanied by concomitant induction of TGF-β1 ligand secretion, and receptor activation.…”
Section: Discussionsupporting
confidence: 92%
“…Bcl-2 is a protein that blocks programmed cell death by controlling mitochondrial apoptosis while The Bax protein, a member of the Bcl-2 family, promotes apoptosis. The ratio of Bax/ Bcl-2 is an indicator of the susceptibility of a cell to undergo apoptosis [ 1 , 35 ]. In our results, TAC increased the renal contents of caspase-3 and Bax proteins and decreased that of Bcl-2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This deposition results from fibroblast differentiation into myofibroblasts that can be promoted by TGF-β 51) and have been regulated by metalloproteinases, lysyl oxidase enzymes, and the EMT process. 52) Consistent with that published by Lim et al 53) our immunohistochemical results have shown a significant increase in tubular expression of ECM proteins including collagen type І, and fibronectin following TAC treatment. One more finding in our study which has not been published elsewhere is that TAC treatment has resulted in an increased tubular expression of TIMP1.…”
Section: Discussionsupporting
confidence: 91%
“…Tac administration induces an increase in blood pressure and plasma creatinine in post-renal transplant patients [ 9 , 10 , 11 ]. Although the precise mechanisms of Tac-induced nephrotoxicity are not entirely comprehended, studies on murine models have revealed that it is linked to acute hemodynamic impairment [ 12 , 13 ]; reduced natriuresis [ 14 ]; elevated proinflammatory lymphocytes [ 15 ]; heightened levels of proinflammatory cytokines; such as IL-6 [ 14 , 15 ]; and the induction of a fibrotic phenotype [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%